CIRCADIAN SLEEP DISORDERS IN SCHOOLCHILDREN OF COUNTRYSIDE SIBERIA - K. A. Gazenkampf; R. K. Omelenchuk; V. N. Emelyanova; N. A. Shnayder; A. N. Alekseeva; O. V. Alekseeva; A. D. Kazantsev; E. P. Fadeeva; D. V. Dmitrenko (Русский журнал детской неврологии, 2017)
Background. Sleep is an important part of a healthy lifestyle, affecting all aspects of human life. Formation of the sleep–wake regime is associated with other physiological processes in the human body. Sleep disorders can lead to the development of various physical and psychological disorders. In schoolchildren and students sleep disorders can lead to memory loss, increase in anxiety and fatigue. Taken together, these factors can lead to lower performance. A variety of internal and external factors can lead to disruption of sleep: stress, much physical and emotional strain, artificial light in the streets, excessive activity of a person during the night (night work, homework etc.). Schoolchildren, living in rural areas, also suffer from sleep disorders. Most of the schoolchildren of countryside are not satisfied with the quality of nocturnal sleep, sleep at least 8 hours a day and notice daytime sleepiness.Objective: to estimate derangements of circadian rhythms of a sleep at schoolchildren of the senior classes, living in countryside.Materials and methods. 67 questionnaires of schoolchildren of the 10th grades of schools of the Abansky District of the Krasnoyarsk Region were analyzed. To estimate the daytime sleepiness, duration and quality of sleep there were used the Child Sleep Questionnaire and the Epworth Sleepiness Scale.Results. A derangements of nocturnal sleep were registered in 52 % of schoolchildren of the 10th grades.Conclusion. Identified sleep disorders in schoolchildren can cause serious damage to their health and cause the development of a serious disorders in the future.